The Reality of Financial Inclusion and its Challenges - Jordan and Algeria as an example - BOUTELLAA, Mohamed; SSAAD BEKHOUCHE, Hassina; Bouguerra, Karima (Finance and Business Economies Review, 2020)
The aim of the study was to present the most important concepts about financial inclusion, its importance and the different ways to enhance it, as well as to identify the most important indicators, taking the example of the reality of financial inclusion in Algeria and Jordan and the most important challenges in the two countries.The study concluded that financial inclusion provides advanced financial services and products, and also plays an important role In mobilizing savings and developing the financial system in the developed countries in general and the developing ones in particular. Despite the strength and development of the financial banking sector in Jordan, there are over 70% of the eligible citizens in Jordan who do not deal with financial institutions despite the existence of an excellent infrastructure that enables citizens and Banks of movement and access to each others, either through traditional branches or through electronic branches. As for Algeria, the ownership of the accounts at the formal financial institutions have improved to an acceptable level, but borrowing from financial institutions is still very low.